2021
DOI: 10.1142/s0219498823500299
|View full text |Cite
|
Sign up to set email alerts
|

Noncatastrophic convolutional codes over a finite ring

Abstract: Noncatastrophic encoders are an important class of polynomial generator matrices of convolutional codes. When these polynomials have coefficients in a finite field, these encoders have been characterized as polynomial left prime matrices. In this paper, we study the notion of noncatastrophicity in the context of convolutional codes when the polynomial matrices have entries in the finite ring [Formula: see text]. In particular, we study the notion of zero left prime in order to fully characterize noncatastrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To be able to study complete MDP convolutional codes, it would be necessary to restrict ourselves to non-catastrophic codes as complete MDP convolutional codes possess a parity-check matrix by definition. However, this would restrict ourselves to free codes, for which it has already been shown that the characterization of MDP convolutional codes is analogue to finite fields [22]. Therefore, we do not consider this special class of codes in this paper.…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations
“…To be able to study complete MDP convolutional codes, it would be necessary to restrict ourselves to non-catastrophic codes as complete MDP convolutional codes possess a parity-check matrix by definition. However, this would restrict ourselves to free codes, for which it has already been shown that the characterization of MDP convolutional codes is analogue to finite fields [22]. Therefore, we do not consider this special class of codes in this paper.…”
Section: 1mentioning
confidence: 99%
“…Remark 7. In [22] noncatastrophic convolutional codes over Z p r are studied. Noncatastrophicity implies that for an encoder G(z), one has that G(0) is full rank, which implies that G(z) is full rank, i.e.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Left factor-prime (rFP) and left zero-prime (rZP) matrices are defined in the same way, upon taking transposes. It can be shown that factor-primeness does not imply zero-primeness but the converse is true [31]. For the purpose of this paper we only need the characterization of zero prime polynomial matrices over…”
Section: Primeness Of Polynomial Matrices Over Z P Rmentioning
confidence: 99%